The role of BRD7 in embryo development and glucose metabolism - Kim, Yoo; Andrés Salazar Hernández, Mario; Herrema, Hilde; Delibasi, Tuncay; Park, Sang Won (Wiley, 2016)
AbstractBromodomain‐containing protein 7 (BRD7) is a member of bromodomain‐containing protein family and its function has been implicated in several diseases. We have previously shown that BRD7 plays a role in metabolic processes. However, the effect of BRD7 deficiency in glucose metabolism and its role in in vivo have not been fully revealed. Here, we report the essential role of BRD7 during embryo development. Mice homozygous for BRD7 led to embryonic lethality at mid‐gestation. Homozygous BRD7 knockout (KO) mice showed retardation in development, and eventually all BRD7 KO embryos died in utero prior to E16.5. Partial knockdown of Brd7 gene displayed mild changes in glucose metabolism.
Keywords: Male; Heterozygote; Chromosomal Proteins, Non-Histone; glucose metabolism; Embryonic Development; Research & Experimental Medicine; Diet, High-Fat; Adenoviridae; bromodomain‐containing protein 7; Pregnancy; Animals; Homeostasis; Insulin; RNA, Messenger; Crosses, Genetic; Mice, Knockout; Gene Expression Regulation, Developmental; Cell Biology; Original Articles; Glucose; Liver; Gene Knockdown Techniques; Embryo Loss; Original Article; embryogenesis; Female; Gene Deletion; 3. Good health